Pengembangan E-Modul Berbasis Flip PDF Professional pada Materi Gaya dan Perubahan Energi Kelas IV SDN Sepatan 3 Kabupaten Tangerang - Fadilah, Ahmad Arif; Latifah, Nur; Safitri, Agustini (MODELING: Jurnal Program Studi PGMI, 2024)
Research with the development of a Professional Flip Pdf based E-Module on Force and Energi Changes for Class IV SDN Sepatan 3 Tangerang Regency in this learning aims to produce a product in the science subject. This development uses the ADDIE model procedure with 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. This development also went through a validation stage with material experts, namely by getting a percentage result of 86% with the criteria "Good", media experts with a percentage score of 89% "Very Good", class teachers with a percentage score of 80% "Good", and the results of the large group trial, namely one class with a total of 44 students, obtained a score of 4.44 and a percentage of 88.8% with the criteria "Very Good/Decent". This is also known from the results of the percentage of E-Module use at 88.8%. and the minimum completeness criteria (KKM) value in science learning in class IV is 75. So the conclusion from the development of E-modules in science learning when using professional flip pdf based E-modules on force and energi changes is that there is a percentage increase of 18 .4%. Based on these results, the Professional Flip Pdf Based E-module media product on Force and Energi Changes Class IV can be said to be Very Good/suitable for use.